2004
DOI: 10.1002/zoo.20011
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of longevity and life expectancy in captive elephants

Abstract: The concepts of longevity (longest lived) and life expectancy (typical age at death) are common demographic parameters that provide insight into a population. Defined as the longest lived individual, longevity is easily calculated but is not representative, as only one individual will live to this extreme. Longevity records for North American Asian elephants (Elephas maximus) and African elephants (Loxodonta africana) have not yet been set, as the oldest individuals (77 and 53 years, respectively) are still al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 8 publications
1
52
0
1
Order By: Relevance
“…Subsequent efforts to address reproductive issues through research (e.g., low fecundity, high neonatal mortality, assisted reproduction) were overshadowed by a comprehensive analysis [Faust et al, 2005a,b] that showed univariate and bivariate approaches (e.g., assisted reproduction with or without importation) would be insufficient to create a positive growth rate. Similar to Wiese and Willis' [2004] study, Faust et al's project was not prioritized by AZA a priori; yet, it resulted in major changes, including prioritized actions in elephant management [e.g., Pittsburgh Zoo and Aquarium's proposed elephant breeding facility, and the National Elephant Breeding Center; also see Conway, 2003]. …”
Section: Elephants As An Example Of Priority Settingmentioning
confidence: 96%
See 1 more Smart Citation
“…Subsequent efforts to address reproductive issues through research (e.g., low fecundity, high neonatal mortality, assisted reproduction) were overshadowed by a comprehensive analysis [Faust et al, 2005a,b] that showed univariate and bivariate approaches (e.g., assisted reproduction with or without importation) would be insufficient to create a positive growth rate. Similar to Wiese and Willis' [2004] study, Faust et al's project was not prioritized by AZA a priori; yet, it resulted in major changes, including prioritized actions in elephant management [e.g., Pittsburgh Zoo and Aquarium's proposed elephant breeding facility, and the National Elephant Breeding Center; also see Conway, 2003]. …”
Section: Elephants As An Example Of Priority Settingmentioning
confidence: 96%
“…In addition, ''experts'' on wild populations of elephants have categorically stated that zoos do not offer appropriate space for elephants. Owing to a glaring lack of information, zoos have been relegated to countering such accusations with ad hoc, largely qualitative citations of ''expertise,'' descriptions of their conservation roles and commitment to elephant welfare and care, and expressions of the need for further research [Smith and Hutchins, 2000;AZA 2001;Hutchins, 2006b]; they have thus far responded with only one rigorous scientific study [which showed that the average life span of zoo elephants was similar to that of free-ranging individuals; Wiese and Willis, 2004].…”
Section: Elephants As An Example Of Priority Settingmentioning
confidence: 99%
“…Unfortunately, as with every aspect of our operation, scientific activities are financially intensive; and the lack of immediate payoff to many research pursuits often makes justification difficult in tight financial times. Additionally, research efforts may appear reactionary to outside forces (e.g., elephant lifespan and other welfare articles in response to PETA, Weise and Willis, 2004). Combined with the at least partial culture of mistrust referred to above, zoo and aquarium researchers often feel they must justify their existence and continually define their role in the zoo or aquarium's overall mission.…”
Section: Valuing and Implementing Science Through Partnershipsmentioning
confidence: 96%
“…3,4 Despite some comparative cancer and lifespan analyses between wild and zoo animals showing that captive animals were susceptible to cancer and decreased longevity. 5,6 Tidière et al 7 revealed that mammals from zoo populations generally lived longer than their wild counterparts (84% of species). Of particular interest, the common hippopotamus (Hippopotamus amphibius), a robust mammal with an estimated 40-year lifespan in nature and with slow pace of life, has increased longevity in captivity.…”
Section: Introductionmentioning
confidence: 99%